A study of English language teachers' professional learning at a time of curriculum reform in Hong Kong - Lim, J (2015)
In the context of a Hong Kong education reform implemented at the new senior secondary level (NSS) in 2009, this research investigates teachers of English as a Second Language (‘English language teachers’) working on subject-specific curriculum renewal. I first conducted two group interviews in summer 2010, at the end of the first year of the implementation of the new senior secondary curriculum in School A. Data from the main study traced this group of teachers into their second year of implementation: between October 2010 and April 2011 I spent a further six months carrying out extensive fieldwork in School A, including two months of intensive classroom observation of two senior secondary teachers of English, using photographs and teacher-talk transcription from classroom teaching to generate interview questions for stimulated recall interviews with the teachers. I also attended bi-weekly (every two weeks) collaborative curriculum design meetings during the entire period of fieldwork. A curriculum advisor employed by the school to work with teachers in designing the new curriculum and resources, as well as mentoring teachers in the context of the reform changes, met with me over three interviews. These enabled me to clarify the purposes of the curriculum innovation within the school, confirm the range of collaborative curriculum design activities on which the teachers were working, investigate how the curriculum changes were initiated, and cross-reference with data generated from other stimulated recall interviews and group interviews. The fieldwork enabled me to establish an understanding of the curriculum changes and innovation at the research site, and via probing questions using photographs and teacher-talk transcriptions I was also able to gain insight into teachers' perceptions of issues related to curriculum change in a reform context. This examination of the psychological process of teacher change formed a window through which to examine the nature of teachers' professional learning. The research followed the teachers at work at a time when reform was underway, and the study recorded a range of curriculum decision-making and curriculum changes. As a former teacher educator I was curious about how these teachers' involvement with curriculum innovation had impacted on their professional learning. This research does not speculate about the kind of professional learning that might have taken place, and nor does it prescribe discrete psychological constructs, such as belief change, knowledge change or attitude change, in order to measure and justify the idea that professional learning had taken place. Rather, the overarching research question concerns how teacher change is relational to both the opportunities and constraints afforded by systemic reform (the 'macro' context), within the collaborative curriculum design team at the institutional, subject-department level (the 'meso' context), and through teachers trying out new pedagogies via curriculum renewal and classroom teaching activities (the 'micro' context). Therefore, this research investigates the underlying psychological process of teacher change at a time of curriculum innovation and examines how teacher change is relational to the affordance in the 'macro', 'meso' and 'micro' environments, which are intrinsically linked to the totality of teachers' professional learning (Opfer & Pedder, 2011). The positioning of teachers' professional learning as affordance is a new conceptualisation offered by this research, using concepts that define professional learning as 'afforded by' and 'relational to' curriculum change and innovation (Gibson, 1979/1986; Stoffregen, 2000, pp.6–8). In addition, this research will utilise analytical procedures to reveal the 'micro-level cognitive process' of teachers' professional learning (Evans, 2014), with a foundation of understanding the psychology of English language teachers grounded in a critical appraisal of previous studies in the sub-field of Language Teacher Cognition (Applied Linguistics). In summary, this research contributes not only locally to the education sector in Hong Kong and the research community in the Asian Pacific Rim, but through adopting a new conceptualisation and examining the psychological process of change of English language teachers enacting curriculum change and innovation, the study reports on findings that will also be relevant to the wider research community in English language teacher education and in-service professional development.